The Pro-fibrotic Response of Mesenchymal Leader Cells to Lens Wounding Involves Hyaluronic Acid, Its Receptor RHAMM, and Vimentin - Menko, A. Sue; Romisher, Alison; Walker, Janice L. (Frontiers in Cell and Developmental Biology, 2022)
Hyaluronic Acid/Hyaluronan (HA) is a major component of the provisional matrix deposited by cells post-wounding with roles both in regulating cell migration to repair a wound and in promoting a fibrotic outcome to wounding. Both are mediated through its receptors CD44 and RHAMM. We now showed that HA is present in the provisional matrix assembled on the substrate surface in a lens post-cataract surgery explant wound model in which mesenchymal leader cells populate the wound edges to direct migration of the lens epithelium across the adjacent culture substrate onto which this matrix is assembled. Inhibiting HA expression with 4-MU blocked assembly of FN-EDA and collagen I by the wound-responsive mesenchymal leader cells and their migration. These cells express both the HA receptors CD44 and RHAMM. CD44 co-localized with HA at their cell-cell interfaces. RHAMM was predominant in the lamellipodial protrusions extended by the mesenchymal cells at the leading edge, and along HA fibrils organized on the substrate surface. Within a few days post-lens wounding the leader cells are induced to transition to αSMA+ myofibroblasts. Since HA/RHAMM is implicated in both cell migration and inducing fibrosis we examined the impact of blocking HA synthesis on myofibroblast emergence and discovered that it was dependent on HA. While RHAMM has not been previously linked to the intermediate filament protein vimentin, our studies with these explant cultures have shown that vimentin in the cells’ lamellipodial protrusions regulate their transition to myofibroblast. PLA studies now revealed that RHAMM was complexed with both HA and vimentin in the lamellipodial protrusions of leader cells, implicating this HA/RHAMM/vimentin complex in the regulation of leader cell function post-wounding, both in promoting cell migration and in the transition of these cells to myofibroblasts. These results increase our understanding of how the post-wounding matrix environment interacts with receptor/cytoskeletal complexes to determine whether injury outcomes are regenerative or fibrotic.